Algorithmic setups for trading popular U.S. ETFs - Gil Cohen (Cogent Economics & Finance, 2020)
In this research, we test whether common trading oscillators can outperform the buy-and-hold strategy (B&H) using six popular ETFs for the period of the last 20 years. We use the original setups of those oscillators and also other setups or oscillators combinations in order to achieve the best past performances. We found that the Relative Strength Index (RSI) combined with Chaikin Money Flow (CMF) gained positive returns for all examined ETFs and also outperformed by 79% the corresponding buy-and-hold strategy for the XLF. The Commodity Channel Index (CCI) and Bollinger Bands (BB) were found to be the best technical tools for trading the examined ETFs. While the CCI performs better for the more volatile ETFs (XLF and XLK), the BB was superior for trading IWM and XLI which are less volatile. We also recommend the CCI strategy for trading the SPY. No technical tools were found to be more effective than B&H strategy for the QQQ.
Keywords: G14; G15; 330; algorithmic; trading; ETFs; oscillators; buy and hold